2016
DOI: 10.1016/j.jtos.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Dexamethasone and Doxycycline on Inflammation and MMP Production in Murine Alkali-Burned Corneas Associated with Dry Eye

Abstract: Alkali burns to the cornea are among the most devastating injuries to the eye. The purpose of this study was to evaluate the effects of dexamethasone (Dex) or doxycycline (Doxy) on protease activity and corneal complications in a combined model (CM) of alkali burn and dry eye. C57BL/6 mice were subjected to the CM for 2 or 5 days (D). Mice were topically treated either with Dex (0.1%), Dox (0.025%) or vehicle QID and observed daily for appearance of corneal perforation. Quantitative real time PCR was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 55 publications
3
58
1
Order By: Relevance
“…To test the hypothesis that blocking NLRP3 would improve clinical parameters and reduce inflammation, alkali-burned corneas were treated with either NaB, HBA, or vehicle for 2 or 5 days post-injury. To compare the relative potency of these molecules, a group of alkali-injured corneas treated with dexamethasone (Dex) was also included, as our previous study showed that Dex is very efficacious in preserving corneal clarity and suppressing inflammation in the most severe model of alkali burn and dry eye [20]. …”
Section: Resultsmentioning
confidence: 99%
“…To test the hypothesis that blocking NLRP3 would improve clinical parameters and reduce inflammation, alkali-burned corneas were treated with either NaB, HBA, or vehicle for 2 or 5 days post-injury. To compare the relative potency of these molecules, a group of alkali-injured corneas treated with dexamethasone (Dex) was also included, as our previous study showed that Dex is very efficacious in preserving corneal clarity and suppressing inflammation in the most severe model of alkali burn and dry eye [20]. …”
Section: Resultsmentioning
confidence: 99%
“…108 Application of topical 0.1% dexamethasone four times per day showed a positive effect in the combined model of alkali burn and desiccating stress, by significantly decreasing mRNA and protein levels of MMP-1, -3, -9 and -13, decreasing MMP-9 gelatinolytic activity and NGAL-MMP-9 complex formation, while causing an impressive improvement in corneal opacification and preventing corneal perforation, compared to saline controls. 98 Studies with gene KO and pharmacologic inhibitors showed that part of the beneficial effects from dexamethasone in this model were through an increase in MMP-8. 84 Nonpreserved topical methylprednisolone administered three to four times per day significantly improved signs and symptoms of dry eye in patients with SS.…”
Section: Corticosteroidsmentioning
confidence: 90%
“…96 Doxycycline increased the rate of corneal epithelial wound healing and decreased MMP-13 and -9 mRNA transcripts, MMP-9 activity and immunoreactivity in the combined model of alkali burn and dry eye. 98 This was accompanied by a decrease in production of neutrophil gelatinase-associated lipocalin (NGAL)-MMP-9 formation and lower levels of IL-1β.…”
Section: Doxycycline and Azithromycin Doxycyclinementioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis of human corneal epithelial cell line (HCEC) after short-term DEX treatment elucidated significant changes in genes regulating cell movement, cytoskeletal remodeling and permeability [36]. Topical DEX treatment indeed was found to preserve corneal clarity and decrease corneal wound healing in a murine model of alkali burned cornea associated with dry eye [37]. DEX significantly reduced the expression of matrix metalloproteases (MMPs) such as MMP1, 3 and 9 as well as interleukin-6 (IL-6) while it increased the expression levels of MMP8, a collagen cleaving enzyme that plays an important role in inflammation and tissue remodeling [38].…”
Section: Introductionmentioning
confidence: 99%